Ferroptosis: A mixed blessing for infectious diseases - Xiao, Leyao; Huang, Huanshao; Fan, Shuhao; Zheng, Biying; Wu, Jianguo; Zhang, Junai; Pi, Jiang; Xu, Jun-Fa (Frontiers in Pharmacology, 2022)
To date, it has been confirmed that the occurrence and development of infectious diseases are tightly associated with regulatory cell death processes, such as apoptosis, autophagy, and necroptosis. Ferroptosis, as a newly discovered form of regulatory cell death characterized by iron-dependent lipid peroxidation, is not only closely associated with tumor progression, but is also found to be tightly related to the regulation of infectious diseases, such as Tuberculosis, Cryptococcal meningitis, Malaria and COVID-2019. The emerging critical roles of ferroptosis that has been found in infectious disease highlight ferroptosis as a potential therapeutic target in this field, which is therefore widely expected to be developed into new therapy strategy against infectious diseases. Here, we summarized the underlying mechanisms of ferroptosis and highlighted the intersections between host immunity and ferroptosis. Moreover, we illuminated the roles of ferroptosis in the occurrence and progression of different infectious diseases, which might provide some unique inspiration and thought-provoking perspectives for the future research of these infectious diseases, especially for the development of ferroptosis-based therapy strategy against infectious diseases.